Synchronized "One-Step" Resection and Cranio-Orbital Reconstruction for Spheno-Orbital Lesions With Custom Made Implant. Issue 5 (July 2021) - Bassi, Massimo; Antonelli, Vincenzo; Tomassini, Alessia; Maimone, Giuseppe; D'Andrea, Marcello; Campobassi, Angelo; Gessaroli, Manlio; Tosatto, Luigino
Abstract : Background: In the last few years, skull base tumors involving the fronto-orbital region have been approached with complex, invasive, and time-consuming cranial reconstruction techniques. On the other hand, recent custom-made implants allow easier and faster procedures, with excellent aesthetic results. The authors propose an easy surgical-planned protocol with a synchronized "one-step" resection and reconstruction of these complex lesions, with a preformed poly-methyilmethacrylate (PMMA) cranioplasty. Methods: Our technique consists of a 2-phases procedure. In the first one, the so-called "virtual" phase, the authors get a tailored 3D-PMMA model based on high-resolution (HR) CT-scans of the patient's skull. Afterward, the authors perform the planned craniotomy on the 3D-PMMA model with the assistance of intraoperative navigation system. Therefore, a further CT-scan of the resected model is performed to develop the final implant. In the second phase, the "surgical phase, " a single procedure consisting in a cranial resection and custom reconstruction is performed with the assistance of stealth-navigation. The authors describe 6 cases of complex fronto-orbital-sphenoidal benign tumors that required skull reconstruction. All patients were examined 3 months after surgery through cosmetic (facial and eyes symmetry and globe position) and ophthalmology tests (visual field, visual impairment, and diplopia). Postsurgical HR CT-scans of the head and MRI-scans of the brain documented a total resection of the tumor and an optimal accuracy of skull reconstruction. Results: In all cases, the authors obtained a highly accurate skull reconstruction following cranio-orbital tumor resection, with a less aggressive and faster procedure compared to autologous bone graft. Final cosmetic and functional results were excellent, with good results in cases of presurgical exophthalmos and orbital asymmetry. None of the patients developed implant-related complications. Conclusions: The "one-step" resection and reconstruction of benign tumors involving the spheno-orbital region with neuronavigation assistance is a technique that allows an accurate tumor removal and a cranial-bone reconstruction within a single surgical procedure, with fewer complications and excellent cosmetic and functional results. Abstract : Supplemental Digital Content is available in the text